Musykilat Talim Al-Qiraah Wa Hulul Lada Tholabah As-Shof ‎Tsamin Fî Al-Madrasah Tsanawiyah Al-Hukumiyah 4 Padang - Ika Wahyu Illahi; Neli Putri (Universitas Islam Negeri Imam bonjol Padang, 2023)
The purpose of Al-Qira’ah learning in general is so that student can ‎reading Arabic well and correctly. To achieve this goal of course, can ‎not be separated from several factors, in terms of linguistic and non ‎linguistic. To get the fact about the existing reality about the ‎‎“problematics of learning Al-Qira’ah and solusions to student class IX in ‎MTsN 4 Padang”, the autor uses several methods, namely methods of ‎interviews, observation, tests and documentation. And to analyze the ‎data that has been collected, the author use a descriptive analysis ‎method. And so that this research can be well directed, the writer uses ‎learning theory and problematic theory in learning Al-Qira’ah. The ‎results of this research is 1) Problematics of Al-Qira’ah learning to ‎student class IX in MTsN 4 Padang in terms linguistic; Student still have ‎difficulty in pronouncing alphabet according the makhraj, Student still ‎have difficulty in short and long voice, Student still have difficulty in ‎differentiate Alif Lam Syamsiyah and Qomariyah. 2) Problematics of Al-‎Qira’ah learning to student class IX in MTsN 4 Padang in terms non ‎linguistic; student interest, low motivation, different student ‎background, low enthusiastic and less confident, the media used is less ‎attractive. 3) Solusions form the problematics of Al-Qira’ah learning to ‎student class IX in MTsN 4 Padang in terms linguistic; train the togue ‎to pronounce correctly, master the science of tajwid, Arabic reading ‎practice. 4) Solusions form the problematics of Al-Qira’ah learning to ‎student class IX in MTsN 4 Padang in terms non linguistic; figthing for ‎learning Al-Qira’ah, get used to reading Al-Qur’an, confident and don’t ‎be afraid of being wrong, the teacher creates a pleasant learning, learn ‎to read thorugh social media‎